Islamic Mutual Funds Promotional Activities: Normal Approximation of Binomial Distribution and Type I Error - Mohd Isa, Mohd Yaziz Bin; Azzahra, Hannan; Mohamed, Zulkifflee (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2019)
The paper applies the normal approximation procedure to a binomial probability distribution. A sample of 392 respondents is surveyed whether they agree or not agree that promotional activities determined the level of awareness of the benefits of Islamic mutual funds. The paper hypothesizes the population mean µ of success effects of promotional activities at 68%, and attempts to reduce Type I error—the probability of rejecting the null hypothesis when it is true. This study reveals that 0.68% of respondents agreed that promotional activities determined the level of awareness of the benefits of Islamic mutual funds. Studi ini menerapkan prosedur perkiraan normal untuk distribusi probabilitas binomial. Survey dilakukan terhadap sampel yang terdiri dari 392 responden untuk mengetahui apakah mereka setuju atau tidak setuju bahwa kegiatan promosi menentukan tingkat kesadaran akan manfaat reksa dana syariah. Hipotesis yang diuji adalah rata-rata populasi µ keberhasilan kegiatan promosi sebnyak 68% dan berupaya untuk mengurangi kesalahan Tipe 1—kemungkinan untuk menolak hipotesis null. Studi ini menemukan bahwa 0.68% dari responded menyetujui bahwa aktifitas promosi menentukan tingkat kesadaran akan manfaat reksadana.